Propofol inhibits pancreatic cancer proliferation and metastasis by up‐regulating miR‐328 and down‐regulating ADAM8. Issue 3 (2nd April 2019) - Yu, Xiangdi; Gao, Yutong; Zhang, Fangxiang
Abstract: Propofol is commonly used for anaesthesia during surgery, and accumulating evidence has demonstrated that propofol is associated with tumour suppression. For example, propofol down‐regulates the expression of vascular endothelial growth factor to inhibit pancreatic cancer malignancy. However, deeper insights into its underlying mechanism are needed. In this study, we treated pancreatic cell lines Panc1 and Bxpc3 with or without propofol. Cell proliferation, migration and invasion were evaluated using 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide and transwell assays. Real‐time polymerase chain reaction was used to measure RNA expression levels. Luciferase assay was performed to determine the transcriptional activity of microRNAs (miRNAs). We found that propofol significantly reduced the proliferation, migration and invasion of pancreatic cancer cells compared to untreated cells. By testing the changes in miRNAs after propofol treatment, propofol was shown to strikingly enhance the expression of miR‐328. Luciferase assays demonstrated that propofol repressed the transcriptional activity of miR‐328, while a disintegrin and metalloproteinase 8 (ADAM8) was a direct target of miR‐328. Knockdown of miR‐328 or ADAM8 led to significantly decreased cell growth and viability. Our results implicate that propofol inhibits pancreatic cancer growth and metastasis by enhancing miR‐328 which targets ADAM8.